Accounting ratios, stock prices, and COVID-19: a study in IBOV companies - Silva, Mateus Barreto Vieira da; Silva, José Erasmo (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Investigate the association between profitability, operational, and liquidity accounting indicators and the reaction of companies’ stock prices after the COVID-19 pandemic. Methodology: The research is empirical and quantitative, involving 51 companies listed in the IBOV index between 2018 and 2022. Data were collected from the Refinitiv Eikon and Economatica systems. A multilevel regression model was used to analyze the data, and statistical tests were conducted using RStudio, Python, and Excel. Results: The results suggest that earnings per share and current liquidity can explain the reaction of stock prices of companies listed in the IBOV. However, the COVID-19 variable did not show statistical significance. Additionally, the effect of COVID-19 was not captured by the year variable. The control variables size and sectors showed significant variability in explaining stock prices. Study Contributions: The study contributes to the literature on the value relevance of accounting information in the capital market during the pandemic. Furthermore, it promotes the use of multilevel regression to analyze sectors in the stock market, providing important insights for investors and stakeholders on the usefulness of profitability and liquidity information for decision-making.